2016
DOI: 10.1002/anie.201609483
|View full text |Cite
|
Sign up to set email alerts
|

High‐Frequency Mechanostimulation of Cell Adhesion

Abstract: Cell adhesion is regulated by molecularly defined protein interactions and by mechanical forces,w hichc an activate ad ynamic restructuring of adhesion sites.P revious attempts to explore the response of cell adhesion to forces have been limited to applying mechanical stimuli that involve the cytoskeleton. In contrast, we here apply anew,oscillatory type of stimulus through push-pull azobenzenes.P ush-pull azobenzenes perform ah igh-frequency,m olecular oscillation upon irradiation with visible light that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…We have shown that the use of light-driven systems is particularly attractive, since such systems allow noninvasive external control with high spatiotemporal precision, as is evident from the rapidly emerging field of photopharmacology (22). Among various approaches to affect cell-surface interaction (1,5), azobenzene-based switches have been applied to modulate protein structure and function (23), and to govern cell or bacterial adhesion (24,25) or direct cell-cell contacts to induce targeted apoptosis in cancer cells (26) upon irradiation with light. However, most of these cell surfaces communicate with the cell's surroundings, and those that do display dynamic behavior, as shown with the spatiotemporal controllable biointerface using an azopolymer (8), translate to microstructures and therefore communicate on a microscopic level rather than on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the use of light-driven systems is particularly attractive, since such systems allow noninvasive external control with high spatiotemporal precision, as is evident from the rapidly emerging field of photopharmacology (22). Among various approaches to affect cell-surface interaction (1,5), azobenzene-based switches have been applied to modulate protein structure and function (23), and to govern cell or bacterial adhesion (24,25) or direct cell-cell contacts to induce targeted apoptosis in cancer cells (26) upon irradiation with light. However, most of these cell surfaces communicate with the cell's surroundings, and those that do display dynamic behavior, as shown with the spatiotemporal controllable biointerface using an azopolymer (8), translate to microstructures and therefore communicate on a microscopic level rather than on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) is ap owerful tool beyond imaging.A FM relies on the sensing of forces and, thus,allows to investigate mechanical properties,that are related to the internal structure of the material. [21][22][23][24] Monitoring the interaction forces while scanning the sample results not only in as urface (two-dimensional) characterization. [25,26] Force Volume measurements allow determining the stiffness as af unction of the threedimensional position.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this assumption, several methods have been described for the application of controlled mechanical stimulation (i.e., temporal, spatial, and amplitude), some of them aiming to verify the positive impact of integrin-mediated adhesion pathways on iPSC reprogramming [113] and differentiation [250, 251]. Although far from being exhaustively described, the pathways seem to be regulated by the change in FA density and local conformation [252], followed by impacting cytoskeleton rearrangement [56], finally regulating cardiomyocyte maturity, e.g., cell-cell contact, sarcomeric structure, and electrical activity. As an example, the interconnection between the mechanical stimulation, in particular shear stress, and the modulation of cellular electrical activity was demonstrated by Roy and Mathew [253], who underlined how the gene encoding the α -subunit of human ether-a-go-go-related gene (hERG) potassium ion channel could be modulated by integrins via a mechanoelectric feedback pathway.…”
Section: Integrin Relevance In Ipsc-derived Cells: In Vitro Biomimmentioning
confidence: 99%